HUBUNGAN KEPERCAYAAN DIRI DENGAN INTERAKSI SOSIAL PADA REMAJA AWAL DI SMP NEGERI 1 GRUJUGAN: The Relationship between Self-Confidence and Social Interaction in Early Adolescents 1 Grujugan Junior High School - Afifah; Suryaningsih, Yeni; Dewi, Sofia Rhosma (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
Self-confidence can be developed through interaction with the environment. Adolescents who have high self-confidence are able to interact more easily with other people, while students who have low self-confidence are less able to interact with other people. Objective: The aim of this research is to determine the relationship between self-confidence and social interaction in early adolescents at SMP Negeri 1 Grujugan. Method: The design of this research is correlation with a cross-sectional approach. The population of this study was 189 respondents from grades 7 and 8. The sample for this study was 128 respondents. The sampling technique used is simple random sampling. The instrument in this research is a questionnaire. Results: From the research it was found that low self-confidence was 46.9%, moderate self-confidence was 33.6%, high self-confidence was 19.5%, low social interaction was 42.2%, medium social interaction was 45.3%, high social interaction was 12 .5%. The results of the Spearman's Rho statistical test with (ɑ = 0.05) showed a p value of 0.000. Conclusion: H1 is accepted, which means there is a relationship between self-confidence and social interaction in early adolescents at SMP Negeri 1 Grujugan, with moderate strength of the relationship (r = 0.404). High self-confidence plays an important role in creating high levels of social interaction for early adolescents.